Hubungan Antara Budaya Organisasi Dengan Disiplin Kerja Pada Badan Kepegawaian Negara Jakarta - Dedy Syahyuni (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Organizational culture is an agreed way to run in any organization or company. Organizational culture is usually not formal in nature, but more consequential to the prevailing custom or conduct. However, there are some companies that are starting to see the importance of organizational culture so they give more emphasis to the implementation of the organizational culture, for example with the slogan, pampfet or posters for mensiosialisasi organizational culture that their personal religious beliefs and they run in the organiasi or his company.Organizational culture in practice not only manage how employees should behave in the Organization to their friends or his superiors only, but organizational culture impact is more than that. Cultural organizations forming the employee attitudes and viewpoints. Employees can work well when shaped by the good of culture organization and employees can also become lazy and have no motivation when they conditioned by cultural organization that are not dynamic, quick and uphold the performance its employees. However there are still many companies that still do not understand the significance of organizational culture. This is a mistake, because from culture organization can build a good employees with the traits or character of the company and can eventually created a work environment that is productive and synergize.This paper is trying to expose the relationship between the organizational culture with the discipline of work of employees in an organization of Government. Questionnaires distributed to the employment bureau in Badan Kepegawaian Negara.From the obtained results of the calculations, there is a relationship of 0.511 and influence of cultural variables Between 0.261 against disciplined work.Key Word: culture organization, discipline of work.